Position of Spanish Unions : memorandum of interview ; Miss F. I. Harris and A. E. Carthy
016b-0015-001 MEMORANDUM OF INTERVIEW. Date November 20, 1937. Time 10.45 am. Reference AC/181 Present Miss F.I. Harris (IFTU) and A.E. Carthy. SUBJECT. POSITION OF SPANISH UNIONS. On Saturday, November 20th, Miss HARRIS, of the I.F.T.U., telephoned to say that Messrs. Schevenels, Stolz and Jouhaux had left for Russia, and that that morning they had received the following telegram: "GENERAL SECRETARY AND TREASURER U.G.T. ARRIVING TODAY IN PARIS AT 3.30 PM URGENTLY DESIRE INTERVIEW BEFORE YOUR DEPARTURE. REQUEST YOU TO FIX APPOINTMENT STAYING HOTEL MODERNE, PLACE REPUBLIQUE. SANTIAGO." I asked Miss Harris when and where the telegram had been handed in. It was handed in at Bordeaux on the 20th (Saturday). Mr. Bolton, when consulted, said he considered the position covered by the IFTU Executive's decision to meet the two groups of the U.G.T. in Paris at the beginning of December. As he was engaged with Mr. Rinner, I telephoned Sir Walter Citrine, who agreed with Mr. Bolton, and said that no responsibility could devolve upon the IFTU if the Spanish comrades arrived in Paris on their own account without making a prior arrangement. He advised the IFTU staff, [not to worry too much about the matter, and] if the Spanish comrades arrived at the office, to interview them, to take a statement, and to send him a report. This was communicated to the IFTU, and Miss HARRIS said that the letter to the UGT conveying the IFTU Executive's decision had been sent on Friday, so that it could not have come to hand before the departure of the Spaniards. 292/946/16b/18(iv)